2024
DOI: 10.1039/d3qm01263h
|View full text |Cite
|
Sign up to set email alerts
|

Applications of amorphous inorganics as novel functional materials

Zhengxi Guo,
Zhaoming Liu,
Ruikang Tang

Abstract: Amorphous inorganics have attracted much attention because of their long-range disordered structure with advantageous functional properties. In this minireview, the novel advances of amorphous inorganics (e.g., metal, metallic oxide, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 222 publications
(335 reference statements)
0
1
0
Order By: Relevance
“…S3†). 47 Spherical aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) coupled with energy-dispersive X-ray spectroscopy (EDS) images indicated that elements of Ni, Co and P are uniformly distributed in the solid phase of A-Ni 0.5 Co 0.5 Pi (Fig. 1d and S4†).…”
Section: Resultsmentioning
confidence: 99%
“…S3†). 47 Spherical aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) coupled with energy-dispersive X-ray spectroscopy (EDS) images indicated that elements of Ni, Co and P are uniformly distributed in the solid phase of A-Ni 0.5 Co 0.5 Pi (Fig. 1d and S4†).…”
Section: Resultsmentioning
confidence: 99%